A new method to quantify air–water gas exchanges in streams based on slug injection and semicontinuous measurement. (22nd July 2020) - Vautier, Camille; Abhervé, Ronan; Chatton, Eliot; Labasque, Thierry; de Dreuzy, Jean‐Raynald
Abstract: Gas exchanges between streams and atmosphere strongly impact biogeochemical cycles, yet their quantification in space and time remains challenging. We propose a new method to measure gas exchange rate coefficients in headwater streams. The method is based on simultaneous slug injections of a conservative tracer and a volatile tracer, coupled to in situ semicontinuous measurements. Its originality lies in the mathematical exploitation of the tracers' breakthrough curves. Taking advantage of the entire breakthrough curves, we infer the gas exchange rate coefficient from a comparative analysis of the shape of the volatile and the conservative breakthrough curves. Tests on synthetic datasets confirmed the validity of the mathematical framework for the whole range of gas exchange rate coefficients found in headwater streams. Field experiments further attested to the real‐world applicability of the method. Salt and helium injections were performed in a first‐order stream and the helium breakthrough curves were obtained using in situ membrane inlet mass spectrometry. This new method allows to determine the gas exchange rates directly in the field, without any external calibration of the data. Its fast implementation enables a wider spatial coverage of the measurements of gas exchange rates, and thus offers an opportunity to improve the large‐scale estimates of CO2 emissions from headwater streams. More generally, our study highlights the informative potential of semicontinuous datasets and encourages further investigation of possible use of temporal signals.